Evaluating Mechanical Properties of Few Layers MoS2 Nanosheets-Polymer Composites - Muhammad Bilal Khan; Rahim Jan; Amir Habib; Ahmad Nawaz Khan (Advances in Materials Science and Engineering)
The reinforcement effects of liquid exfoliated molybdenum disulphide (MoS2) nanosheets, dispersed in polystyrene (PS) matrix, are evaluated here. The range of composites (0~0.002 volume fraction (Vf) MoS2-PS) is prepared via solution casting. Size selected MoS2 nanosheets (3~4 layers), with a lateral dimension L 0.5~1 µm, have improved Young’s modulus up to 0.8 GPa for 0.0002 Vf MoS2-PS as compared to 0.2 GPa observed for PS only. The ultimate tensile strength (UTS) is improved considerably (~×3) with a minute addition of MoS2 nanosheets (0.00002 Vf). The MoS2 nanosheets lateral dimension and number of layers are approximated using atomic force microscopy (AFM). The composites formation is confirmed using X-ray diffraction (XRD) and scanning electron microscopy (SEM). Theoretical predicted results (Halpin-Tsai model) are well below the experimental findings, especially at lower concentrations. Only at maximum concentrations, the experimental and theoretical results coincide. The high aspect ratio of MoS2 nanosheets, homogeneous dispersion inside polymer, and their probable planar orientation are the possible reasons for the effective stress transfer, resulting in enhanced mechanical characteristics. Moreover, the micro-Vickers hardness (HV) of the MoS2-PS is also improved from 19 (PS) to 23 (0.002 Vf MoS2-PS) as MoS2 nanosheets inclusion may hinder the deformation more effectively.